Cassava mosaic geminiviruses in Africa - Legg, James P.; Fauquet, Claude M. (2004)
Cassava mosaic disease (CMD) caused by cassava mosaic geminiviruses (CMGs) (Geminiviridae:Begomovirus) is undoubtedly the most important constraint to the production of cassava in Africa at the outset of the 21st century. Although the disease was recorded for the first time in the latter part of the 19th century, for much of the intervening period it has been relatively benign in most of the areas where it occurs and has generally been considered to be of minor economic significance. Towards the end of the 20th century, however, the inherent dynamism of the causal viruses was demonstrated, as a recombinant hybrid of the two principal species was identified, initially from Uganda, and shown to be associated with an unusually severe and rapidly spreading epidemic of CMD. Subsequent spread throughout East and Central Africa, the consequent devastation of production of the cassava crop, a key staple in much of this region, and the observation of similar recombination events elsewhere, has once again demonstrated the inherent danger posed to man by the capacity of these viruses to adapt to their environment and optimally exploit their relationships with the whitefly vector, plant host and human cultivator. In this review of cassava mosaic geminiviruses in Africa, we examine each of these relationships, and highlight the ways in which the CMGs have exploited them to their own advantage.